(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This paper delves into the realms of feminist critiques and will review the roles of women in Shashi Deshoande’s numerous fiction like ‘The Binding Vine’[1], ‘That Long Silence’[2], ‘A Matter Of Time[3]’ and many more. It is believed that this study will be able to describe the patriarchal constructs that defined women's roles and identities during the time the story was composed. The study analyzes the way all the fiction showcases that, to maintain their power, men have created boundaries and obstacles for women, thus making it even harder for women to retain power. Pragmatic evidence and critical analysis of oppressions, controls, and limited securities created for women in traditional societies are depicted in this paper. Furthermore, how societal conservative norms would affect the preferences made by characters and influence their relationship and identity are further researched. Supporting a thorough analysis of the chosen fictions, the current research will contribute to both feminist criticism studies and the representation of women in traditional societies in comparison to the current scenarios. This series therefore aims to delve into the deeper complexities of gender dynamics and societal expectations and thereby search for ways in which one might seek a conclusive understanding of how these structures challenge women and how literature conveys and sustains them.